Association between serum anion gap and all-cause mortality in critically ill patients with diabetic kidney disease: Analysis of the MIMIC-IV database - Yu-Nan Han; Cheng-Yue Xiong; Yong-Xiang Wang; Jun-Li Yuan; Lin Li; Zui-Xuan Xiao (PLoS ONE, 2025)
Background Diabetic kidney disease (DKD) is one of the most common diabetic complications and is closely related to metabolic acidosis. The serum anion gap (AG), an important index of acid-base balance, may reflect disturbed metabolism and be correlated with increased mortality risk. However, the role of AG in all-cause mortality risk in individuals suffering from severe DKD is not yet clear. Methods In this study, patients identified with a diagnosis of severe DKD utilizing MIMIC-IV database were determined. They were subsequently divided into four quartiles based on their serum AG levels. The findings consisted of in-hospital deaths and ICU deaths. The relationship between serum AG levels of severe DKD patients and clinical outcomes was elucidated using Cox proportional hazards regression analysis and RCS analysis. Results In total, 1,716 patients (66.43% male) received treatment, with in-hospital and ICU mortality rates reaching 16.43% and 13.17%, respectively. Multivariate Cox regression analysis revealed that elevated serum AG levels were remarkably linked to all-cause mortalities. When adjusted for confounders, elevated serum AG levels correlated notably with in-hospital mortality [HR = 1.09(95%CI:1.07,1.11)P < 0.0001] and ICU mortality [HR = 1.10(95%CI:1.07,1.12)P < 0.0001]. RCS analysis showed that serum AG levels were positively correlated in a linear fashion with all-cause death risk. Conclusion Serum AG shows a significant positive correlation with all-cause mortalities in hospitals and ICU settings among patients with severe DKD. This suggests that serum AG could serve as a potential indication for recognizing DKD individuals with an increased overall risk of all-cause death.